Maksimalisasi Desain Embung Sebagai Sumber Air Irigasi Untuk Memenuhi Kebutuhan Air Tanaman Tebu - Amril Ma'ruf (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
PT. Perkebunan Nusantara VII (Persero) is one of State Owned that took task from Government to realize the Revitalization National Sugar Programme. To support this program, needed improvement expansion of sugarcane area in one of work unit of PTPN 7 called Bunga Mayang. There are 385 units Embung in Bunga Mayang’s area and felt not sufficient to irrigate existing sugarcane area especially in Disrict 1, while the presumably very large potential for ground water. Therefore, its necessary of Embung design based of sugarcane water requirements with efficient method to resolve the issue. The results Unila Research Institute in 2009 showed water requirements of sugarcane crop in District 1 on the plot 183 is 0,168 m. Conditions of water deficit occurs from mid-June until mid-December. Design of flood discharge of 100-year period 4,203 m3/dtk. Based on the data, made Embung urugan type with Maximum design capacity of rainwater and surface runoff is 26.090,21 m3. The analysis showed that the capacity of the embung was only able to serve a total area of 7.76 hectares of the 9.9 hectare service. To maximize the capacity, then made excavation buttom of embung 1 until 4 meters. The analysis showed that thepotential discharge resulting greater from soil water that is 4.182 m3/day, 3.943,78 m3/day,3.585,25 m3/day, 3.346,24 m3/day, and 2.987,71 m3/day each in June, July, August, September and October respectively. Service from Embung design is increase up to 171,773 ha. Thus, the design of Embung can be considered a maximum design because not only able to serve 183 plot area (9,9 ha), but also capable to irrigate other plot area near to the Embung location until 85 ha.